IL-27 effects on HIVGag-specific CD4 and CD8 T cell function - Abdussamad, Maryam; Katz, Grace; Cheng, Jie; Mehta, Chinmayee; Andres-Martin, Fernando; Mahmood, Danial; Kumar, Princy; Catalfamo, Marta (Frontiers in Virology, 2025)
BackgroundIn people with HIV (PWH) and suppressed viral replication by antiretroviral therapy persistent T cell activation and inflammation are important contributors of the increased risk of morbidity and mortality. CD8 T cells express checkpoint receptors and are dysfunctional. IL-27, a member of the IL-6/IL-12 family has shown anti-viral properties against various human viruses, including HIV. The role of IL-27 on HIV-specific T cells remains unclear. We hypothesized that IL-27 will enhance the function of HIV-specific T cells.MethodsIL-27 effects on T cell function was evaluated by measuring cytokine secretion, proliferation, and cytotoxicity. ResultsOur findings show that IL-27 upregulates cytokine secretion and cytotoxic potential, and trafficking of proliferating HIV-specific CD8 T cells expressing checkpoint receptors TIGIT and PD-1. Unbiased clustering analysis showed that IL-27 may have differential effects on distinct populations of HIV-specific T cells. ConclusionAltogether these results suggest that IL-27 may enhance T cell function in the setting of chronic HIV infection.